PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN - Yushita Marini; Nisha Marina (Center for Research and Community Service (LPPM) University of Abulyatama, 2017)
This study aimed to get empirical evidence regarding the corporate governance mechanism proxied by the size of the board of commisioners, independent directors, the size of the board of directors and audit committees that affect the value of the company. This study using purposive sampling method for collecting samples of the companies listed in Indonesia Stock Exchange that publish the complete annual financial statements for 2010-2014, have the data necessary corporate governance in research, the company has never delisted and present its financial statements in Indonesian Rupiah , From the analysis of the study showed that the size of the board of commisioners, independent directors, and the size of the board of directors affect the value of the company, while the audit committee does not affect the value of the company.